The optimal retraction problem and solutions of integrodifferential systems - Muglia, Luigi; Marino, Giuseppe; Canino, Annamaria (My University, 2014)
In this Ph.D thesis we study the following topics related to fixed point theory: (A) Existence of solutions for integro-differential systems with or without impulses. (B) The optimal retraction problem and minimal displacement problem. The contributions to the first topics appear in the following papers: • G. Marino, P. Pietramala, L. Muglia, Impulsive neutral integrodifferential equations on unbounded intervals, Mediterr. J. Math. 1 1 (2004) 93–108 • G. Marino, P. Pietramala, L. Muglia, Impulsive neutral semilinear equations on unbounded intervals, Nonlinear Funct. Anal. Appl. 9 4 (2004) 527–543 • G. Marino, V. Colao, L. Muglia, A note on weakly isotone maps and common solutions for differential systems, Acta Math. Sin. (English series), 22 4 (2006) 1171-1174 The contribution to the second topics appear in the following paper: • G. Goebel, G. Marino, L. Muglia, R. Volpe, The retraction constant and the minimal displacement characteristic of some Banach spaces, to appear in Nonlinear Analysis TMA i
Dottorato di Ricerca in Matematica ed Informatica,XXVII Ciclo, 2006-2007
Keywords: Analisi matematica; Analisi differenziale; Sistemi complessi